Low-thermal-damage multi-principal-element alloy-based diamond composite material and preparation method thereof

Through the composite and laser 3D printing technology of Ti diamond plated with multi-main alloy matrix, the existing deep hole drill bit materials have been solved in the low performance problem in high temperature and high pressure environments, and the effect of low thermal damage, enhanced mechanical properties and improved wear resistance is achieved.

CN119800193APending Publication Date: 2025-04-11JIANGSU WUXI MINERAL EXPLORATION MASCH GENERAL FAB CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411721714.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing deep-hole drill bit materials are difficult to meet the multiple functional requirements of strength, toughness, rock crushing capacity, cooling performance and life in high temperature and high pressure environments. The traditional processing technology is low in efficiency and high cost, making it difficult to be used for the formation of complex structural components.

Method used

The low-thermal damage multi-main alloy foundation diamond composite material is used to combine Ti diamond with multi-main alloy matrix, combined with laser 3D printing technology, powder composition and laser forming process are optimized to form a nearly fully dense composite material.

Benefits of technology

Low-level thermal damage of diamond particles is achieved, the comprehensive mechanical properties of composite materials are enhanced, the wear resistance and service life are improved, and the thermal stress and cost of material forming are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800193A_ABST
    Figure CN119800193A_ABST
Patent Text Reader

Abstract

According to the low-thermal-damage multi-principal-element alloy-based diamond composite material and the preparation method thereof, diamond particles are plated with Ti, direct contact between the diamond particles and a high-temperature molten pool is effectively prevented, and therefore the situation that graphitization and multi-principal-element alloy matrixes still exist in a single FCC phase after laser melting and solidification is avoided, and the thermal damage of the multi-principal-element alloy-based diamond composite material is reduced. The composition uniformity can be kept, and good interface bonding is formed with diamond particles with in-situ carbide interface layers. And the mechanical property of the composite material is further enhanced by regulating and controlling the components of the multi-principal element alloy. And meanwhile, by optimizing all parameters of laser scanning in 3D printing forming, local heat accumulation and thermal stress are reduced, and thermal damage to the diamond is reduced. In the prior art, wettability of diamond and metal melt is poor, and the diamond is subjected to thermal damage under the action of high-energy laser.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of diamond composite materials, and in particular relates to a low-heat-damage multi-principal-element alloy-based diamond composite material. Background Art

[0002] Energy and mineral resources are important pillars supporting the development of my country's national economy. With the large-scale exploitation of mineral resources, related exploration work has gradually shifted from the past shallow (<500m) and medium-deep (500-1000m) to deep (>1500m) and even ultra-deep (>3000m). However, deep drilling faces a series of complex and harsh working conditions such as high temperature (150-400℃), high pressure (100-150MPa), and high-hardness crystalline rock, which puts higher requirements on the strength, toughness, rock crushing ability, cooling performance and life of deep hole drill bits, and urgently needs to seek new breakthroughs and innovations in drill bit material composition and macro / micro structure design.

[0003] At present, deep hole drill bits are mainly impregnated diamond drill bits, which have relatively simple geometric configurations and lack complex structures such as porous bodies and internal flow channels, as well as special microstructures such as orderly arrangement of diamond abrasives and gradient distribution of material composition. It is difficult to meet the needs of multiple functions such as chip holding, cooling, and stress relief of components. The traditional processing technology based on hot pressing and sintering has a long cycle, low efficiency, high cost, and is difficult to use for the forming of complex structural components, which seriously restricts the innovative development of new deep hole drill bits. Laser 3D printing technology, based on the principle of laminated manufacturing, can give the component itself great design freedom and novel microstructure, and is expected to provide key solutions for the development of high-performance complex configuration diamond drill bits and their material-structure-function integrated manufacturing.

[0004] In terms of drill bit material development, as drilling depth increases and rock formations become more complex and changeable, the formula design of diamond drill bit metal binders needs to fully consider the broad-spectrum requirements, and the diversification of component types has become an important development trend. As typical multi-principal alloy materials, medium / high entropy alloys are highly compatible / matched with diamond due to their "high entropy effect" and "diffusion inertia" as well as excellent mechanical properties, namely high strength, high toughness, high wear resistance, and high hardness. They are one of the most promising metal matrix candidate materials for the development of new diamond deep hole drill bits. However, considering that diamond has poor wettability with metal melt during laser forming, and diamond is extremely susceptible to thermal damage caused by direct laser irradiation and instantaneous high temperature of the molten pool, how to avoid thermal damage to diamond under the action of high-energy lasers and achieve high-strength interface bonding of multi-principal alloys / diamond is a key challenge. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a multi-principal alloy-based diamond composite material with low thermal damage.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: the composite material is composed of Ti-plated diamond and a multi-principal alloy matrix;

[0009] The multi-principal alloy matrix is ​​an FCC phase and contains a large number of dispersed rod-shaped or granular L1 2 Nano-coherent precipitation strengthening phase, the interface thickness between the diamond and the multi-principal alloy matrix is ​​1.6-4.8 μm; the addition amount of the Ti-plated diamond is 10-20 vol% of the multi-principal alloy matrix; the specific composition of the multi-principal alloy is (CoCrNi) x Al y Ti y , where x+y+y=100, and x is 82 to 94.

[0010] As a preferred solution of the low thermal damage multi-principal element alloy-based diamond composite material described in the present invention, wherein: the average thickness of the Ti is 0.28-0.46 μm.

[0011] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a low-thermal-damage multi-principal-element alloy-based diamond composite material.

[0012] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0013] The high-purity Ti powder and diamond particles are fully mixed to obtain a mixed powder, the mixed powder is heated under vacuum conditions by a vacuum evaporation method, and the product is sieved after cooling to obtain Ti-plated diamond particles;

[0014] The Ti-plated diamond particles and the multi-principal alloy powder are mixed evenly, placed in a ball mill, evacuated and introduced with argon gas, and then intermittently ball-milled to obtain a diamond / multi-principal alloy composite powder;

[0015] Finally, the composite powder was laser 3D printed through three-dimensional solid modeling, path planning, slicing, layer-by-layer powder laying and laser scanning solidification.

[0016] As a preferred solution of the method for preparing the low-heat-damage multi-principal-element alloy-based diamond composite material of the present invention, the temperature of the heating treatment is 800-900° C., and the time of the heating treatment is 1.5-3 hours.

[0017] As a preferred solution of the method for preparing the low thermal damage multi-principal element alloy-based diamond composite material of the present invention, the gas pressure of the argon gas is controlled at 0.4-0.6 MPa.

[0018] As a preferred solution of the method for preparing the low thermal damage multi-principal component alloy-based diamond composite material of the present invention, wherein: the ball milling speed is 250-300 r / min, and the ball milling time is 2-3 h.

[0019] As a preferred solution of the method for preparing the low thermal damage multi-principal component alloy-based diamond composite material described in the present invention, wherein: the thickness of the powder layer in the layer-by-layer powder spreading is 30 μm.

[0020] As a preferred scheme for the preparation method of the low thermal damage multi-principal element alloy-based diamond composite material described in the present invention, wherein: the volume energy density is η=P / (vdh), wherein P is the laser power, v is the scanning speed, d is the powder layer thickness, and h is the scanning spacing.

[0021] As a preferred embodiment of the method for preparing the low thermal damage multi-principal alloy-based diamond composite material of the present invention, the laser power of the laser scanning solidification is 120-160W, the scanning speed is 400-600mm / s, the scanning spacing is 50μm, and the volume energy density is 133.33-266.67J / mm 3 .

[0022] As a preferred scheme for the preparation method of the low-thermal-damage multi-principal-element alloy-based diamond composite material described in the present invention, the laser scanning solidification strategy is a combination of strip scanning and interlayer scanning vector rotation, the strip width is 4 mm, and the interlayer rotation angle is 45 to 90°.

[0023] As a preferred solution of the method for preparing the low-thermal-damage multi-principal-element alloy-based diamond composite material of the present invention, the substrate preheating temperature is set at 200-205° C. during the laser scanning solidification.

[0024] Beneficial effects of the present invention:

[0025] (1) The diamond / multi-principal alloy composite material provided by the present invention is obtained by forming a composite powder of Ti-plated diamond and multi-principal alloy through powder bed laser 3D printing. The optimized powder composition and laser forming process ensure the nearly full density of the final formed part and the low level of thermal damage to the diamond particles;

[0026] (2) Diamond / multi-principal alloy composite powders are composed of Ti-coated diamond and a multi-principal alloy matrix. The Ti-coated diamond particles can combine with the carbon atoms diffused in the diamond to form carbides in the high-temperature dynamic molten pool induced by laser, thereby effectively preventing the direct contact between the diamond particles and the high-temperature molten pool and avoiding the graphitization of the diamond particles; while the multi-principal alloy matrix still exists as a single FCC phase after laser melting and solidification, which can maintain the uniformity of the composition. The presence of Cr and Ti elements also provides the possibility of forming a good interface with the diamond particles with an in-situ carbide interface layer. At the same time, by effectively regulating the internal alloy composition (the composition of Al and Ti), the harmful brittle phases (Heusler and Laves phases) in the laser formed structure can be further suppressed and the beneficial strengthening phases (L1 2 phase), thereby enhancing the comprehensive mechanical properties of the composite material;

[0027] (3) Through the rational control of laser energy density and the optimization of scanning strategy, the thermal damage of diamond can be reduced while reducing local heat accumulation and thermal stress. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0029] Figure 1 This is a flow chart for preparing the diamond / multi-principal alloy composite material in Example 1 of the present invention.

[0030] Figure 2 This is a SEM image of the interface between diamond and substrate inside the laser 3D printed sample prepared in Example 1 of the present invention.

[0031] Figure 3 This is a SEM image of the interface between diamond and substrate inside the laser 3D printed sample prepared in Example 2 of the present invention.

[0032] Figure 4 This is a SEM image of the interface between diamond and substrate inside the laser 3D printed sample prepared in Example 3 of the present invention.

[0033] Figure 5 This is a SEM image of the internal structure of the laser 3D printed sample prepared in Comparative Example 1 of the present invention.

[0034] Figure 6 This is a SEM image of the interface between diamond and substrate inside the laser 3D printed sample prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0035] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0036] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0037] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0038] The purity of the diamond particles used in the present invention is 99.99%, and the average particle size range is 20 μm.

[0039] The purity of Ti used in the present invention is 99.999%.

[0040] Unless otherwise specified, the raw materials used in the present invention are all commercially available in the art.

[0041] The method for measuring the wear resistance of the low-heat-damaged multi-principal alloy-based diamond composite material of the present invention is as follows: a high-speed reciprocating friction tester is used to test the friction coefficient of the sample, and a Si with a diameter of 3 mm is selected. 3 N 4 The ball was used as the friction pair, and the friction and wear test was carried out at room temperature with a load of 50 N, a friction time of 30 min, a friction speed of 150 mm / s, and a stroke of 5 mm.

[0042] Example 1

[0043] This embodiment provides a method for preparing a multi-principal alloy-based diamond composite material with low thermal damage, specifically:

[0044] (1) High-purity Ti (purity 99.999%) powder and diamond particles are fully mixed to obtain a mixed powder. The mixed powder is heated at 800° C. for 2.4 h under vacuum conditions by a vacuum evaporation method. After cooling, the product is sieved to obtain Ti-plated diamond particles.

[0045] (2) Ti-plated diamond particles and multi-element alloy ((CoCrNi) 88 Al 6 Ti 6 ) powders were mixed evenly in a volume ratio of 1:9, put into a ball mill, evacuated and introduced with argon, and the air pressure was controlled at 0.4 MPa; then intermittent ball milling was carried out with a ball-to-material ratio of 2:1, a ball milling speed of 300 r / min, and a ball milling time of 2 h to obtain diamond / multi-principal alloy composite powders.

[0046] (3) Finally, laser 3D printing was performed, wherein the laser power was 120 W, the scanning speed was 600 mm / s, the scanning interval was 50 μm, and the powder layer thickness was 30 μm. At this time, the volume energy density was 133.33 J / mm 3 The substrate was preheated to 200°C, and the laser scanning adopted a strategy of strip scanning and interlayer scanning vector rotation. The strip width was 4 mm and the interlayer rotation angle was 45°.

[0047] Example 2

[0048] This embodiment provides a method for preparing a multi-principal alloy-based diamond composite material with low thermal damage, specifically:

[0049] (1) High-purity Ti (purity 99.999%) powder was fully mixed with diamond particles, and then the mixed powder was placed in a vacuum furnace and heated at 850° C. for 1.5 h under vacuum conditions. After the treatment was completed, the temperature was lowered and the resulting product was sieved to obtain Ti-coated diamond particles.

[0050] (2) Ti-plated diamond particles and multi-element alloy ((CoCrNi) 82 Al 9 Ti 9 ) powders are mixed in a volume ratio of 1.5:8.5 and placed in a ball mill. The ball mill is evacuated and then introduced with argon gas, and the gas pressure is controlled at 0.5 MPa; the mixed powders are then intermittently ball-milled with a ball-to-material ratio of 2:1, a ball milling speed of 250 r / min, and a ball milling time of 2 h to finally obtain diamond / multi-principal alloy composite powders.

[0051] (3) In the subsequent laser 3D printing process, the laser power is 140 W, the scanning speed is 500 mm / s, the scanning interval is 50 μm, and the powder layer thickness is 30 μm. At this time, the volume energy density is 186.67 J / mm 3 The substrate was preheated to 200°C, and the laser scanning adopted a strategy of strip scanning and interlayer scanning vector rotation. The strip width was 4 mm and the interlayer rotation angle was 67°.

[0052] Example 3

[0053] This embodiment provides a method for preparing a multi-principal alloy-based diamond composite material with low thermal damage, specifically:

[0054] (1) High-purity Ti (purity 99.999%) powder is fully mixed with diamond particles, and then the mixed powder is placed in a vacuum furnace and heated at 900°C for 3 hours under vacuum conditions. After the treatment is completed, the temperature is lowered and the resulting product is sieved to obtain Ti-coated diamond particles.

[0055] (2) Ti-plated diamond particles and multi-element alloy ((CoCrNi) 94 Al 3 Ti 3 ) powders are mixed in a volume ratio of 2:8 and placed in a ball mill. The ball mill is evacuated and then introduced with argon gas, and the gas pressure is controlled at 0.6 MPa; the mixed powders are then intermittently ball-milled with a ball-to-material ratio of 2:1, a ball milling speed of 250 r / min, and a ball milling time of 2 h to finally obtain diamond / multi-principal alloy composite powders.

[0056] (3) In the subsequent laser 3D printing process, the laser power is 160W, the scanning speed is 400mm / s, the scanning interval is 50μm, and the powder layer thickness is 30μm. At this time, the volume energy density is 266.67J / mm 3 The substrate was preheated to 200°C, and the laser scanning adopted a strategy of strip scanning and inter-layer scanning vector rotation. The strip width was 4 mm, and the inter-layer scanning vector rotation angle was 90°.

[0057] Comparative Example 1

[0058] The difference between this comparative example and Example 3 is that the diamond particles are not plated with Ti, and the rest of the preparation process is the same as that of Example 3.

[0059] The positions of the interfaces between diamond and substrate in the samples prepared in Examples 1 to 3 and Comparative Example 1 were measured. The results are shown in Tables 1 and Figures 2 to 5 shown.

[0060] Table 1 Interface thickness between diamond and substrate in samples

[0061]

[0062] (Note: / indicates that a large amount of carbide dendrite phase is generated and cannot be effectively combined)

[0063] From Table 1 and Figures 2 to 5 It can be seen that the interface thickness between the Ti-plated diamond and the multi-principal alloy matrix reaches up to 4.7μm, indicating that the interface bonding of the composite material is good. This may be because the multi-principal matrix still exists as a single FCC phase after laser melting and solidification, which can maintain the uniformity of the composition. The presence of Cr and Ti elements also promotes better bonding between the multi-element alloy matrix and the Ti-plated diamond particles with an in-situ carbide interface layer, thus having a higher interface thickness.

[0064] Raman tests were performed on the samples prepared in Examples 1 to 3 and Comparative Example 1, and the obtained peak intensity ratios of diamond to graphite are shown in Table 2.

[0065] Table 2 Raman peak intensity ratio of diamond and graphite in the samples

[0066]

[0067] As can be seen from Table 2, the diamond-to-graphite peak intensity ratio of the composite material prepared by Ti-plated diamond particles and multi-principal alloy is higher, indicating that Ti plating on diamond particles can reduce the formation of graphite. This is because the Ti-plated diamond surface combines with the carbon atoms in the diamond to form carbides in the high-temperature dynamic molten pool induced by the laser, which effectively hinders the direct contact between the diamond particles and the high-temperature molten pool, thereby avoiding the graphitization of the diamond particles.

[0068] The friction and wear tests were carried out on the surfaces of the samples prepared in Examples 1 to 3 and Comparative Example 1, and the friction coefficients of the surfaces of the samples were obtained as shown in Table 3.

[0069] Table 3 Friction coefficient of sample surface

[0070]

[0071] It can be seen from Table 3 that, on the one hand, the presence of Ti coating can reduce the thermal damage on the surface of diamond particles and maintain the angularity and high hardness of the surface of diamond particles. On the other hand, the introduction of Ti coating can further increase the Ti content of the matrix based on element diffusion, which helps to inhibit the harmful brittle phase (Heusler and Laves phase) inside the laser formed organization and stabilize the beneficial strengthening phase (L1 2In addition, it can be clearly seen that the composite material surface friction coefficient prepared by Ti-plated diamond particles is lower than that of non-Ti-plated diamond particles, indicating that Ti plating can improve the wear resistance of the composite material and make it have a longer service life.

[0072] Comparative Example 2

[0073] The difference between this comparative example and Example 3 is that the laser power in the laser process parameters is adjusted to 200 W, and the volume energy density is 333.33 J / mm 3 The rest of the preparation process is the same as that in Example 3.

[0074] The interface position between diamond and substrate in the sample prepared in Comparative Example 2 was measured, and the results are shown in Table 4 and Figure 6 shown.

[0075] Table 4 Interface thickness between diamond and substrate in samples

[0076]

[0077] (Note: / indicates that a large amount of carbide dendrite phase is generated and cannot be effectively combined)

[0078] According to Table 4 and comparison Figure 4 and Figure 6 It can be seen that the increase of laser power will lead to excessive laser energy input, which in turn promotes the formation of a large number of carbide dendrite phases, and almost no complete diamond particles are retained in the formed sample.

[0079] The sample prepared in Comparative Example 2 was subjected to Raman testing, and the peak intensity ratio of diamond to graphite obtained is shown in Table 5.

[0080] Table 5 Raman peak intensity ratio of diamond to graphite in the samples

[0081]

[0082] It can be seen from Table 5 that the composite material prepared from Ti-plated diamond particles and multi-principal alloy has a higher peak intensity ratio of diamond to graphite, indicating that the formation of graphite can be reduced under reasonable laser energy input. This is because excessive laser energy input will accelerate the diffusion and migration of carbon atoms in diamond, and at the same time, the laser ablation effect is enhanced, which intensifies the graphitization of diamond particles.

[0083] The surface of the sample prepared in Comparative Example 2 was subjected to a friction and wear test, and the friction coefficient of the sample surface was obtained as shown in Table 6.

[0084] Table 6 Friction coefficient of sample surface

[0085]

[0086] It can be seen from Table 6 that too high laser energy input produces more serious diamond graphitization, which weakens the reinforcement effect of diamond and increases the surface friction coefficient of the prepared composite material, thereby reducing the wear resistance of the composite material.

[0087] In summary, the present invention obtains a diamond / multi-principal alloy composite material by powder bed laser 3D printing. By plating Ti on diamond particles, the direct contact between diamond particles and the high-temperature molten pool is effectively hindered, thereby avoiding graphitization. The multi-principal alloy matrix still exists as a single FCC phase after laser melting and solidification, which can maintain the uniformity of the composition and form a good interface with the diamond particles with an in-situ carbide interface layer. The mechanical properties of the composite material are further enhanced by regulating the composition of the multi-principal alloy.

[0088] At the same time, by optimizing the parameters of laser scanning in 3D printing, local heat accumulation and thermal stress are reduced, and thermal damage to diamond is reduced. This is different from the existing technology where diamond has poor wettability with metal melt and thermal damage to diamond occurs under the action of high-energy laser.

[0089] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A low thermal damage multi-principal alloy-based diamond composite material, characterized in that: The composite material is composed of Ti-plated diamond and a multi-principal alloy matrix; The multi-principal alloy matrix is ​​an FCC phase and contains a dispersed rod-shaped or granular L12 nano-coherent precipitation strengthening phase. The interface thickness between the diamond and the multi-principal alloy matrix is ​​1.6-4.7 μm. The addition amount of the Ti-plated diamond is 10-20 vol% of the multi-principal alloy matrix. The specific composition of the multi-principal alloy is (CoCrNi) x Al y Ti y , where x+y+y=100, and x is 82 to 94.

2. The method for preparing the low thermal damage multi-principal alloy-based diamond composite material according to claim 1, characterized in that: include, The high-purity Ti powder and diamond particles are fully mixed to obtain a mixed powder, the mixed powder is heated under vacuum conditions by a vacuum evaporation method, and the product is sieved after cooling to obtain Ti-plated diamond particles; The Ti-plated diamond particles and the multi-principal alloy powder are mixed evenly, placed in a ball mill, evacuated and introduced with argon gas, and then intermittently ball-milled to obtain a diamond / multi-principal alloy composite powder; Finally, the composite powder was laser 3D printed through three-dimensional solid modeling, path planning, slicing, layer-by-layer powder laying and laser scanning solidification.

3. The method for preparing the low thermal damage multi-principal alloy-based diamond composite material according to claim 2, characterized in that: The temperature of the heating treatment is 800-900°C.

4. The method for preparing the low thermal damage multi-principal alloy-based diamond composite material according to claim 2, characterized in that: The heating treatment time is 1.5 to 3 hours.

5. The method for preparing the low thermal damage multi-principal alloy-based diamond composite material according to claim 2, characterized in that: The pressure of the argon gas is controlled at 0.4-0.6 MPa.

6. The method for preparing the low thermal damage multi-principal alloy-based diamond composite material according to claim 2, characterized in that: The ball milling speed is 250-300 r / min.

7. The method for preparing the low thermal damage multi-principal alloy-based diamond composite material according to claim 2, characterized in that: The ball milling time is 2 to 4 hours.

8. The method for preparing the low thermal damage multi-principal alloy-based diamond composite material according to claim 2, characterized in that: The laser power of the laser scanning curing is 120-160W, the scanning speed is 400-600mm / s, and the volume energy density is 133.33-266.67J / mm 3 .

9. The method for preparing the low thermal damage multi-principal alloy-based diamond composite material according to claim 2, characterized in that: The strategy of laser scanning solidification is a combination of strip scanning and inter-layer scanning vector rotation, and the inter-layer scanning vector rotation angle is 45 to 90 degrees.

10. The method for preparing the low thermal damage multi-principal alloy-based diamond composite material according to claim 2, characterized in that: The preheating temperature of the substrate for laser scanning curing is set at 200-220°C.